Major Impact of Coping Styles on Anxiety and Depression Symptoms in Healthcare Workers During the Outbreak of COVID-19 - Wang, Dongke; Chen, Jie; Liu, Xinghuang; Jin, Yan; Ma, Yanling; Xiang, Xuelian; Yang, Ling; Song, Jun; Bai, Tao; Hou, Xiaohua (Frontiers in Psychology, 2022)
Background: In the early days of COVID-19 outbreak，the normally orderly health system was severely challenged by large numbers of feverish patients and shortage of healthcare workers. The outbreak played a harmful role on the mental health of these healthcare workers. Objective: We aim to assess the prevalence of moderate/severe anxiety and depression symptoms (ADS) of healthcare workers in different regions during COVID-19 disaster and identify the potential risk factors. Methods: We did a cross-sectional study on ADS of healthcare workers in epicenter-Hubei province and regions in lower epidemic-other provinces by questionnaire online. The data of ADS, the demographic characteristics, occupational exposure, physical condition, family situation and coping styles were collected and analyzed. Result: 24.68% of the respondents had experienced moderate/severe ADS. Moderate/severe ADS were in a higher prevalence in Hubei (32.39%) than other provinces (18.22%). Suspicious symptoms on their own and in family members were independent risk factors of moderate/severe ADS of all health workers. Working on the frontline was the independent risk factor for participants in Hubei province, while quarantine was independent risk factor for those in other provinces. Moreover, among all participants, those with negative coping style were more than four times more likely to have moderate/severe ADS than those with positive coping style. Conclusion: Moderate/severe ADS were in a higher prevalence in healthcare workers of Hubei province during COVID-19 outbreak. The coping style may have major impact on ADS in such situation.